2019
DOI: 10.1177/0706743719839314
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Implementing a Model of Mental Healthcare Involving Trained Lay Health Workers in Treating Major Mental Disorders Among Youth in a Conflict-Ridden, Low-Middle Income Environment: Part II Results

Abstract: Objectives: To report the outcomes of young people (aged 14-30 years) treated for major mental disorders in a lay health worker (LHW) intervention model in a rural district of conflict-ridden Kashmir, India. Methods: Over a 12-month follow-up, LHWs collected data on symptoms, functioning, quality of life and disability, and patients’ and families’ service engagement and satisfaction. Results: Forty trained LHWs (18 males and 22 females) identified 262 individuals who met the criteria for a diagnosis of a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Twenty-three (59%) studies provided interventions that addressed common mental disorders (CMD) (24, 25, 29, 34-36, 38, 39, 41-43, 47-49, 52, 54, 55, 57, 67-71), five (13%) addressed severe mental illness (26,27,30,37,40), and 10 studies (26%) addressed both common and severe illnesses (28,31,33,44,45,49,50,53,56,58). Thirty-six studies (92%) provided training to participants face-to-face (24-28, 31, 33-58, 67-70) and eight (21%) used digital technology and web-based training (24, 28-30, 50, 67, 68, 71).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-three (59%) studies provided interventions that addressed common mental disorders (CMD) (24, 25, 29, 34-36, 38, 39, 41-43, 47-49, 52, 54, 55, 57, 67-71), five (13%) addressed severe mental illness (26,27,30,37,40), and 10 studies (26%) addressed both common and severe illnesses (28,31,33,44,45,49,50,53,56,58). Thirty-six studies (92%) provided training to participants face-to-face (24-28, 31, 33-58, 67-70) and eight (21%) used digital technology and web-based training (24, 28-30, 50, 67, 68, 71).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Training interventions were commonly delivered by multidisciplinary teams (n = 12, 31%) comprising of psychiatrists, psychologists, counsellors, and social workers (25,26,28,30,33,37,41,49,56,67,69,70). Six studies (15%) were delivered by a psychiatrist (27,32,34,40,50,53), two (5%) by a psychologist (36,71), and one (3%) by a social worker (35).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the skill on psychological first aid will help ASHAs in coping with their stress, and anxiety as well as the community they are serving. Psychological first aid training was found to be an important skill during the Ebola crisis in Sierra Leone and had a positive impact [ 33 ]; closer to home, a study with lay health workers providing mental health counselling was found to have an impact, although the role of such training in the mental well-being of workers themselves was not explored [ 7 ]. Concurrently, we also believe that having access to psychosocial support services such as counselling during and after the conflict will help ASHAs to take responsibility for their lives and the community at large.…”
Section: Discussionmentioning
confidence: 99%
“…Conflict-affected health systems in countries like Afghanistan, Burkina Faso have also engaged CHWs to provide essential services under restrictive and sometimes dangerous situations [ 6 ]. In India, we found one study demonstrating the effectiveness of a lay health worker intervention in a rural conflict ridden district of Kashmir state [ 7 ], and another showing feasibility of community health worker supported tuberculosis patient tracing using GeneXpert in naxal conflict affected border areas of Chhattisgarh state [ 7 , 8 ]. However, in neither case were ASHA workers involved even as they are employed in all of the conflict -affected regions of india, which include the erstwhile state of Jammu and Kashmir as well as six of the eight states in the northeast region.…”
Section: Introductionmentioning
confidence: 99%